P04.17 Antigen heterogeneity in glioblastoma cell lines, patient-derived cells, and patients' glioblastoma tissue is an obstacle for CAR-T cell therapy development. (9th September 2021) - Dufner, V; Schulz, E; Monoranu, C; Hudecek, M; Ernestus, R; Hagemann, C; Löhr, M; Nerreter, T
Abstract: BACKGROUND: Immunotherapy targeting surface antigens, e.g. CAR-T-cell therapy has become a promising therapeutic approach for glioblastoma (GBM) treatment. Antigen heterogeneity constitutes a major obstacle not only for preclinical in vitro studies but also for clinical translation. Here, we provide information about the surface expression of the eight in GBM CAR-T-cell therapy most targeted antigens (GD2, CSPG4, CD133, CD70, HER2, Il13Rα2, EGFRvIII and EphA2) by analyzing GBM cell lines (GCL), patient-derived cells (PDCL) and patients' tumor tissue (PT) and comparing the expression profiles. MATERIAL AND METHODS: We measured expression of the above-mentioned antigens in 7 GCL (GaMG, U87, U373, U343, U251, U138, DKMG), 7 PDCL and PT of 9 patients by flow cytometry (FACSCanto II). After evaluation with FlowJo software (TreeStar), we scored antigen expression (0–1.0: low expression, 1.1–2.0: medium expression, 2.1–3.0: high expression) and calculated the mean expression and range. RESULTS: GD2 showed a medium expression in GCL (x̅=1.3) but was highly expressed in PDCL (x̅=2.6) and PT (x̅=2.4). In contrast, CSPG4 displayed low expression in GCL (x̅=0.3) and PT (x̅=0.4), but medium expression in PDCL (x̅=1.9). CD133, a stem cell marker, showed low expression in GCL (x̅=0.8) and PDCL (x̅=0.4), whereas the expression in PT was medium (x̅=1.4). Both CD70 and Il13Rα2 were weakly expressed in GCL, PDCL and PT (x̅=0.2, 0.4, 0.0 and 0.5, 0.6, 0.4, respectively). HER2 displayed medium expression in GCL (x̅=1.4) and PDCL (x̅=1.4) and low expression in PT (x̅=0.6). For EGFRvIII medium expression was detectable in all three entities (x̅=1.4, 1.1 and 1.1). EphA2 was mildly expressed in GCL (x̅=0.1), medium expressed in PT (x̅=2.0) and highly expressed in PDCL (x̅=2.6). Overall, there was high variability of antigen surface expression even within each of the groups. CONCLUSION: GCL, PDCL and PT display heterogenic antigen surface expression with high variability within each group, thereby complicating clinical translation of in vitro results obtained using cell lines. This aspect should be taken into account in GBM target antigen research.